An investigation of moderators of a precision teaching and frequency building intervention. Issue 2 (3rd July 2021) - Mc Tiernan, Aoife; Holloway, Jennifer; Healy, Olive; Kubina, Richard M.
ABSTRACT: Research examining behavioural fluency to date has demonstrated positive outcomes in relation to the efficacy of such interventions to increase the rate of correct responding with targeted mathematics skills. Equally as important is the necessity to investigate potential moderators of behavioural fluency so that the most effective instructional approaches can be implemented. The current study investigated the ability of individual differences and implementation variables to moderate outcomes of a frequency building intervention targeting mathematics skills with 71 participants. Participant age, grade, gender, standardised measures of mathematical ability, pre-intervention rates of correct responding with instructional materials, and intervention intensity were investigated as moderating variables. Participant age, pre-test rates of correct responding, and intervention intensity demonstrated the greatest ability to moderate intervention outcomes. The findings are discussed in relation to the importance of matching frequency building interventions to individual students' needs.